Will childcare subsidies increase the labour supply of mothers in Ireland? - Karina Doorley; Dora Tuda; Luke Duggan (University of Essex, Institute for Social and Economic Research (ISER), 2023)
The cost of childcare has a significant impact on the decision of parents - particularly mothers - to work. Prior to the introduction of subsidies for formal childcare in Ireland in 2019 through the National Childcare Scheme (NCS), the cost of full-time centre-based childcare was among the most expensive in the OECD. In this paper, we investigate the effects of the scheme on the labour supply and childcare choices of mothers. We model the joint decision of labour supply and childcare for lone and coupled mothers of children under six. Mothers are likely to respond to the introduction of childcare subsidies in 2019 by switching from informal childcare to formal childcare (11ppt), but not by increasing their participation in the labour market. A hypothetical abolition of all childcare costs would close the gender employment gap, increasing mothers' participation by 30 ppt.
Keywords: J13; J22; C25; 330; female labour supply; childcare; discrete choice